Who’s That in Charge? It’s Jenny Wren, “The Person of the House” - Schotland, Sara D. (Disability Studies Quarterly, 2009)
While several Dickens characters fit binary stereotypes of the disabled (pitiful/helpless; monstrous/villainous), Jenny Wren, the dolls’ dressmaker in Our Mutual Friend,(1864-5),creates a unique and constructive life overcoming her infirmities. This essay considers her successful adaptation and argues that in several respects she reverses and challenges the limits ordinarily imposed on disabled women in Victorian fiction. Jenny Wren anticipates today’s view that the disabled and the able-bodied can work together in interdependent relationships, subverting the expectation that the disabled are inevitably dependent. While typically the disabled woman in the Victorian novel is denied a reproductive future, Jenny is an exception. Dickens was ahead of his time in providing a suitor for Jenny, and envisioning that a disabled woman can be beautiful.